Seasonal Water Exchanges between China’s Poyang Lake and Its Saucer-Shaped Depressions on River Deltas - Guiping Wu (Water, 2017)
The saucer-shaped depressions located at the river deltas of Poyang Lake are typical floodplain shallow sub-lakes subject to river-lake connection or isolation. The hydrological connectivity between these depressions and the main lake has a major influence on the hydrologic function and ecological integrity of the lake-floodplain and associated wetland habitats. This study explored the water level fluctuations and water exchange processes between the Poyang Lake and three typical saucer-shaped depressions, using a 30-min temporal resolution of water level observations during 2015–2016. Our results showed that the water level correlation and hydrological connectivity between the main lake and its depressions displayed a strong seasonal and spatial signal. Temporally, the rainfall significantly influences the seasonality and frequency of water level fluctuations both in the main lake and the depressions. The correlation coefficient of the water level ordered from high to low occurred during the high-water period, the rising-water period, the falling-water period and the low-water period, respectively. Spatially, depressions with a shorter connection duration to the main lake are located at higher local elevation and at larger geographical distance from the main lake. Finally, we also discussed the implications of these findings and possible factors that could have caused these particular water regime characteristics and water exchange processes.